2003
DOI: 10.1046/j.1365-2222.2003.01583.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related T cell responses to allergens in childhood

Abstract: These findings suggest that grass pollen sensitivity in childhood is accompanied by a progressive accumulation of allergen-primed T cells and progressive deviation of the allergen-induced cytokine response towards a Th2 response in atopic subjects throughout childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Exposure and sensitization to HDM is likely to occur constantly very early in life, even at 1 month of age (32) while exposure to ryegrass usually occurs intermittently throughout childhood and teenage years (33, 34). A recent study (35) found a significant age‐related proliferative response to ryegrass allergens, but not to HDM, and an increased age‐related Th2 deviation among ryegrass‐sensitive but not HDM‐sensitive atopic subjects. Thus there may be a greater influence of later childhood factors in the development of ryegrass sensitization than HDM sensitization.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Exposure and sensitization to HDM is likely to occur constantly very early in life, even at 1 month of age (32) while exposure to ryegrass usually occurs intermittently throughout childhood and teenage years (33, 34). A recent study (35) found a significant age‐related proliferative response to ryegrass allergens, but not to HDM, and an increased age‐related Th2 deviation among ryegrass‐sensitive but not HDM‐sensitive atopic subjects. Thus there may be a greater influence of later childhood factors in the development of ryegrass sensitization than HDM sensitization.…”
Section: Discussionmentioning
confidence: 96%
“…This timing of allergen exposure together with the later age of fish consumption may allow a larger window of opportunity for PUFA immunomodulation for ryegrass than HDM. Thus, as the time of consolidation of Th2 responses to different aeroallergens varies with T‐cell memory for HDM allergens being established in early childhood and for ryegrass allergens throughout childhood (35), the ‘usual’ introduction of fish into diet might be too late to protect against HDM‐sensitization developed in early life. A parallel‐group RCT involving high‐risk newborns found no effect of ω ‐3‐rich fish oil supplements on overall sensitization to aeroallergens and HDM sensitization at 18 months (36).…”
Section: Discussionmentioning
confidence: 99%
“…Like other organs directly relevant to cough (e.g. systemic and mucosal immune system) [26,27] or not directly related to cough (e.g. renal system), one can speculate that the cough reflex has maturational differences as well.…”
Section: Why Adult Type Definitions Are Not Appropriatementioning
confidence: 99%
“…Antigen-specific IgE responses are under the control of cytokines produced by competing signals from distinct subsets of T helper (Th) cells [1]. Interleukin (IL)-4 is essential for the development of Th2 cells, which induce IgE production, eosinophilia, and, with sustained generation, the progression of sensitization and allergic inflammation [2,3]. The Th2 responder phenotype is universal at an early age, as polarization of the cytokine profile away from cell-mediated Th1-type immunity towards humoral immunity of the Th2-type prevails in utero [4].…”
Section: The Allergic Infantmentioning
confidence: 99%